Antibiofilm efficacy of zwitterionic 2-methacryloloxyethyl phosphorylcholine (MPC) polymer coatings against Vibrio fischeri - Murchana Sarma; Ryan P.O’ Hara; Ashfaqul Hoque Khadem; Manas D. Warke; Lihua Lou; Ayse Asatekin; Debora F. Rodrigues (Water Research, 2026)

The COSPAR international space weather action teams (ISWAT) initiative: a driving force for the COSPAR space weather roadmap - Maria M. Kuznetsova; Mario M. Bisi; Hermann J. Opgenoorth; Martin A. Reiss; M. Leila Mays; Lucilla Alfonsi; C. Nick Arge; David Barnes; Anna Belehaki; Thomas E. Berger; Amanda Brecht; Sean Bruinsma; et al. (Advances in Space Research, 2026)

Jute bags as a sustainable alternative to single-use plastic bags in Bangladesh: Rethinking the sole reliance on life cycle assessment - M.F.R. Zuthi; F. Khan; I. Lange; S. Kühlewindt; T.T. Jarin; M.H. Masum; M.A. Rahman; N. Tasnim; E. Kraft; A. Hoque; K.M. Hassan (Sustainable Production and Consumption, 2025)

Mosquitoes Reared in Nearby Insectaries at the Same Institution Have Significantly Divergent Microbiomes - Laura E. Brettell; Ananya F. Hoque; Tara S. Joseph; Vishaal Dhokiya; Emily A. Hornett; Grant L. Hughes; Eva Heinz (Environmental Microbiology, 2025)
The microbiome influences critical aspects of mosquito biology and variations in microbial composition can impact the outcomes of laboratory studies. To investigate how biotic and abiotic conditions in an insectary affect the composition of the mosquito microbiome, a single cohort of Aedes aegypti eggs was divided into three batches and transferred to three different climate‐controlled insectaries within the Liverpool School of Tropical Medicine. The bacterial microbiome composition was compared as mosquitoes developed, the microbiome of the mosquitoes' food sources was characterised, environmental conditions over time in each insectary were measured, and mosquito development and survival were recorded. While developmental success was similar across all three insectaries, differences in microbiome composition were observed between mosquitoes from each insectary. Environmental conditions and bacterial input via food sources varied between insectaries, potentially contributing to the observed differences in microbiome composition. At both adult and larval stages, specific members of the mosquito microbiome were associated with particular insectaries; the insectary with less stable and cooler conditions resulted in a slower pupation rate and higher diversity of the larval microbiome. These findings underscore that even minor inconsistencies in rearing conditions can affect the composition of the mosquito microbiome, which may influence experimental outcomes.

Correction to: Monitoring and prediction of land use land cover change of Chittagong Metropolitan City by CA-ANN model - I. Islam; K. F. Tonny; M. Z. Hoque; H. M. Abdullah; B. M. Khan; K. H. S. Islam; F. A. Prodhan; M. Ahmed; N. T. Mohana; J. Ferdush (International Journal of Environmental Science and Technology, 2024)

Monitoring and prediction of land use land cover change of Chittagong Metropolitan City by CA-ANN model - I. Islam; K. F. Tonny; M. Z. Hoque; H. M. Abdullah; B. M. Khan; K. H. S. Islam; F. A. Prodhan; M. Ahmed; N. T. Mohana; J. Ferdush (International Journal of Environmental Science and Technology, 2024)

Knowledge and practice of antimicrobial usage and resistance among poultry farmers: A systematic review, meta-analysis, and meta-regression - Abdullah Al Sattar; Nurun Nahar Chisty; Nusrat Irin; Md. Helal Uddin; F M Yasir Hasib; Md. Ahasanul Hoque (Veterinary Research Communications, 2023)

Environmental Consequences of Intensive Aquaculture Practices at Moyna Purba Medinipur West Bengal India with Special Reference to Carbon Footprint and Carbon Sequestration - S. Adhikari; R. N. Mandal; B. N. Paul; F. Hoque; A. Das; A. Hussan; D. N. Chattopadhyay; P. P. Chakrabarti; G. S. Saha; P. K. Sahoo (Bulletin of Environmental Contamination and Toxicology, 2023)

Two amino-acid polymorphisms in PBP4 generate penicillin tolerance in group B streptococcus - H. Kim; B. Fittipaldi; F. Hoque; C. Wang; O. Zefi; W. Li; Z. Goldman; Y. Peter; P. Basu (Vegetos, 2022)

Drinking water vulnerability to climate change and alternatives for adaptation in coastal South and South East Asia - M. A. Hoque; P. F. D. Scheelbeek; P. Vineis; A. E. Khan; K. M. Ahmed; A. P. Butler (Climatic Change, 2016)

SH3GL2 is frequently deleted in non-small cell lung cancer and downregulates tumor growth by modulating EGFR signaling - Santanu Dasgupta; Jin Sung Jang; Chunbo Shao; Nitai D. Mukhopadhyay; Upneet K. Sokhi; Swadesh K. Das; Mariana Brait; Conover Talbot; Rex C. Yung; Shahnaz Begum; William H. Westra; Mohammad Obaidul Hoque; et al. (Journal of Molecular Medicine, 2013)

Factors limiting the health of semi-scavenging ducks in Bangladesh - M. A. Hoque; L. F. Skerratt; A. J. C. Cook; S. A. Khan; D. Grace; M. R. Alam; A. Vidal-Diez; N. C. Debnath (Tropical Animal Health and Production, 2011)

Monitoring the health and production of household Jinding ducks on Hatia Island of Bangladesh - M. A. Hoque; L. F. Skerratt; M. A. Rahman; M. A. Alim; D. Grace; B. Gummow; A. B. M. Rabiul Alam Beg; N. C. Debnath (Tropical Animal Health and Production, 2011)

Factors limiting traditional household duck production in Bangladesh - M. A. Hoque; L. F. Skerratt; M. A. Rahman; A. B. M. Rabiul Alam Beg; N. C. Debnath (Tropical Animal Health and Production, 2010)

Effect of pineapple disease on germination and yield contributing parameters of some promising varieties of sugarcane - F. Begum; M. I. Talukder; M. Z. Hoque (Sugar Tech, 2008)

Dissociation (Ds) constructs, mapped Ds launch pads and a transiently-expressed transposase system suitable for localized insertional mutagenesis in rice - Narayana M. Upadhyaya; Qian-Hao Zhu; Xue-Rong Zhou; Andrew L. Eamens; Mohammad S. Hoque; Kerrie Ramm; Ramannee Shivakkumar; Kathryn F. Smith; Shu-Ting Pan; Suzhi Li; Kefan Peng; Song J. Kim; et al. (Theoretical and Applied Genetics, 2006)

Effect of hydrogen sulphide on liver somatic index and Fulton's condition factor in Mystus nemurus - M. T. Hoque; F. M. Yusoff; T. Law; M. A. Syed (Journal of Fish Biology, 1998)
The growth rate and liver somatic index were significantly ( P Mystus nemurus exposed to hydrogen sulphide compared to controls. These differences increased with corresponding increases in hydrogen sulphide concentrations. No significant differences ( P >0.05) in Fulton's condition factor were detected between the exposed fish and the controls. The results revealed that liver somatic index is a more sensitive indicator of hydrogen sulphide toxicity compared to Fulton's condition factor.